Implementasi Prinsip-Prinsip Tata Kelola yang Baik dan Perannya terhadap Kinerja di Badan Usaha Milik Desa (BUMDes) - Hafiez Sofyani; Uji Nury Nur Azlin Ali; Dovi Septiari (Jurnal Ilmiah Akuntansi, 2020)
This study aims to investigate the extent to implementation of transparency, responsiveness, professionalism, rule of law, and vision strategies have been implemented and then contribute to performance of Village-Owned Enterprises (BUMDes). This study used on explorative qualitative approach with the interview methods conducted on four Village-Owned Enterprises (BUMDes) in Special Region of Yogyakarta by involving the director, staff, headman, and the local community members as resource. The result of this study found that governance practices with the principles of transparency, responsiveness, professionalism, rule of law, and vision strategies can influence the performance of Village-Owned Enterprises (VOE). This study gives us the knowladge about governance practice literature and its role in efforts to achieve performance in Village-Owned Enterprises.